Differential expression of heat shock protein genes in sorghum (Sorghum bicolor L.) genotypes under heat stress - Pavli, O. I.; Ghikas, D. V.; Katsiotis, Andreas; Skaracis, G. N. (My University, 2011)
Various types of sorghum were subjected to thermal stress to reveal the mode of expression of genes of the heat shock protein (hsp) family. In silico sequence determination of hsp genes in related cereal species led to the selection of appropriate primers for PCR amplification of a segment corresponding to the hsp90 gene from sorghum. Deduced sequence information allowed the design of gene specific primers for quantification of hsp90 gene expression by means of real-time quantitative polymerase chain reaction (RT-qPCR). Fourteen days-old plants were exposed to a temperature of 47°C for a time period ranging from 10 to 180 min. Total RNA was extracted from stressed and control plants and subjected to reverse transcription and RT-qPCR analysis. The actin gene was used as an internal standard. Gene expression was assessed by using cDNA from all types of plant material and for all the different durations of heat stress exposure. Data from RT-qPCR analyses were analyzed using REST software. The highest level of hsp90 gene expression was realized upon exposure to heat for either 60 or 30 min, while expression levels differed among the genotypes studied. In addition, overall levels of hsp90 gene expression were significantly different among varieties tested. Information of such genotypic variation in expression levels of hsp90 gene under heat stress, coupled with related field performance data, could potentially be exploited in breeding programs.
Keywords: Abiotic stress; Heat shock proteins; Hsp90; Plant breeding; Sorghum